Retinoblastoma Outcomes Based on the 8th Edition American Joint Committee on Cancer Pathological Classification in 1411 Patients - Vempuluru, VS (2024)
Purpose: To evaluate the outcomes of retinoblastoma (RB) based on the 8th edition of the American Joint Committee on Cancer (AJCC) pathological classification in a global cohort of patients. Design: Retrospective, multicenter, intercontinental, collaborative study. Participants: A total of 1411 patients. Intervention: Primary enucleation with or without adjuvant chemotherapy or radiotherapy. Main Outcome Measures: Orbital tumor recurrence, tumor-related metastasis, and tumor-related death. Results: According to the 8th edition AJCC pathological classification, 645 eyes (46%) belonged to pathological T (pT)1, 164 (11%) to pT2, 493 (35%) to pT3, and 109 (8%) to pT4 categories. At a mean follow-up of 38 months (median, 35 months; < 1–149 months), orbital tumor recurrence was seen in 8 (1%), 5 (3%), 22 (4%), and 25 (23%) of pT1, pT2, pT3, and pT4 (P < 0.001) categories, respectively; tumor-related metastasis was seen in 7 (1%), 5 (3%), 40 (8%), and 46 (43%) of pT1, pT2, pT3, and pT4 (P < 0.001) categories, respectively; tumor-related death was seen in 12 (2%), 7 (4%), 64 (13%), and 64 (59%) of pT1, pT2, pT3, and pT4 (P < 0.001) categories, respectively. Multivariate Cox proportional hazards analysis of outcomes revealed pT category and adjuvant therapy as independent predictors of outcomes. Categories pT3b (P = 0.005), pT3c (P < 0.001), pT3d (P < 0.001), and pT4 (P < 0.001) had a greater hazard for orbital recurrence; categories pT2a (P = 0.015), pT3a (P < 0.001), pT3b (P < 0.001), pT3c (P < 0.001), pT3d (P < 0.001), and pT4 (P < 0.001) had a greater hazard for tumor-related metastasis; and categories pT2a (P = 0.068), pT2b (P = 0.004), pT3a (P < 0.001), pT3b (P < 0.001), pT3c (P < 0.001), pT3d (P < 0.001), and pT4 (P < 0.001) had a greater hazard for tumor-related death when compared with the pT1 category. Patients who did not receive adjuvant therapy had greater hazards of orbital tumor recurrence in categories pT3b (P = 0.005), pT3c (P = 0.003), and pT4 (P = 0.002); greater hazards of tumor-related metastasis in categories pT3a (P = 0.001), pT3b (P = 0.01), pT3c (P = 0.001), and pT4 (P = 0.007); and tumor-related death in categories pT3a (P < 0.001), pT3b (P = 0.009), pT3c (P = 0.018), and pT4 (P < 0.001) when compared with those who received adjuvant therapy. Conclusions: The 8th edition AJCC pathological classification predicts outcomes in patients undergoing primary enucleation for RB, and adjuvant therapy is associated with a lower risk of orbital recurrence, tumor-related metastasis, and tumor-related death in the pT3 and pT4 categories. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.